Richard III / [videorecording (DVD)] - Olivier, Laurence, 1907-1989; Olivier, Laurence, 1907-1989; Olivier, Laurence, 1907-1989; Hardwicke, Cedric, 1893-1964; Gielgud, John, 1904-2000; Huson, Paul; Shine, Andy; Haye, Helen, 1874-1957; Brown, Pamela, 1917-1975; Richardson, Ralph, Sir, 1902-1983; Clunes, Alec; Naismith, Laurence, 1908-1992; et al. (Criterion collection ;, 2013)
Richard, Duke of Gloucester through a set of murderous machinations, steals the crown from his brother Edward.